2006
DOI: 10.1021/ac061674g
|View full text |Cite
|
Sign up to set email alerts
|

pH-Independent Fluorescent Chemosensor for Highly Selective Lithium Ion Sensing

Abstract: Since lithium salts are used as pharmaceutically active compounds against manic-depressive psychosis, there is a demand to monitor the lithium concentration in blood in the narrow range of 0.6-1.2 mM effectively and safely. Here we report on an optical sensor approach for the determination of Li+, based on the design and synthesis of a novel lithium fluoroionophore KLI-1 and its polymer immobilizable derivative KLI-2, and the application to an optode. The novel lithium fluoroionophores rely on a tetramethyl "b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(46 citation statements)
references
References 31 publications
(46 reference statements)
0
45
1
Order By: Relevance
“…The response times of the sensor in a continuous sample flow mode were recorded by placing a mesoporous silica thin-film coated round-shaped glass disc in a small-volume flow cell constructed in our laboratory. 16 Samples were delivered to the flow cell in a constant flow of 1 mL/min using a peristaltic pump SJ-1211H (ATTO Corp., Tokyo, Japan) system. Figure 1 shows the synthesis scheme for the preparation of the pH optode.…”
Section: Reagents and Instrumentsmentioning
confidence: 99%
“…The response times of the sensor in a continuous sample flow mode were recorded by placing a mesoporous silica thin-film coated round-shaped glass disc in a small-volume flow cell constructed in our laboratory. 16 Samples were delivered to the flow cell in a constant flow of 1 mL/min using a peristaltic pump SJ-1211H (ATTO Corp., Tokyo, Japan) system. Figure 1 shows the synthesis scheme for the preparation of the pH optode.…”
Section: Reagents and Instrumentsmentioning
confidence: 99%
“…Due to their high sensitivity, ultra-fast response, and the compatibility of instrumentation with the biological environment, the fluorescence sensing devices are gaining increased attention for the analysis of metal ions over other methods. Metal cation recognition is very important for quantification of blood electrolytes [2], cations involved in ion-channel transportation [3], or for monitoring of lithium [4] and potassium [2] levels in the treatment of bipolar disorder and hypertension, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Spectrofluorimetric techniques [31,32] rely upon the reaction of lithium to a specific fluoroionophore however, to the authors' knowledge; their functionality using blood samples has not been demonstrated yet. Spectrophotometric techniques [33] make use of specific dyes which react with lithium causing a shift in light absorbance wavelengths.…”
Section: ) Optical Methodsmentioning
confidence: 99%